Modeling foreign investment received in the colombian oil sector during the period 1996-2016 - Callazo Antúnez, Ana María; Meñaca Guerrero, Indira; Lechuga Cardozo, Jorge Isaac; Medina Carrascal, HéctorJosé; Uribe Urán, Carlos Mario; Barragán Morales, Camilo Enrique (2019)

(untitled)
Foreign direct investment received in the oil sector in Colombia is a dependent variable, based on percentages with respect to GDP of exports of goods and services, and gross capital formation as independent. This work highlights the oil sector within the Colombian economy and the important role that foreign investors have had in this sector. The link between this variable and another macroeconomic variable was identify within the parameters marked within the model of multiple linear regression. This research is quantitative, of an explanatory type and is framed within the paradigm of structuralism. In this research work, the SPSS statistical program for modeling is implemented and the econometric model of direct foreign investment of the Colombian oil sector between 1996 and 2016 is sought.